Are analyst stock recommendation revisions more informative in the post-IFRS period? - Charitou, Andreas; Karamanou, Irene; Kopita, Anastasia (My University, 2018)
This paper investigates whether the mandatory IFRS adoption has affected the informativeness of analyst recommendation revisions in Europe. Although prior studies document that IFRS adoption improved analyst forecast attributes, the impact of IFRS cannot be completely assessed without examining how the market reacts to information-rich events in an environment with enhanced disclosure. To examine this question we utilize a difference-in-differences design using as main control sample firms that had voluntarily adopted IFRS before the EU's mandated switch. Overall, our evidence suggests that after the mandatory adoption of IFRS, both analyst upgrades and downgrades are more informative. These results hold after controlling for a number of variables that capture analyst, firm and information environment characteristics and are robust to a number of sensitivity analyses including the use of a US control sample. Finally, we examine whether our results are sensitive to the level of accounting enforcement. We find that analyst downgrades are more informative in the post-IFRS period for firms in both high and low enforcement environments. Analyst upgrades, however, are more informative only if they are issued for firms in high enforcement countries.
Keywords: Disclosure; Enforcement; Financial analysts; IFRS; Informativeness; Recommendations